Uprowadzenie jako forma realizacji polityki ekstradycyjnej na przykładzie sprawy United States v. Alvarez-Machain - Dyjak, Daniel (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The legality of the abduction being one of most controversial substitutes for extradition is the subject of recognition of national courts of each country. The core issue of the United States vs. Alvarez-Machain case ruled in 1992 by the U.S. Supreme Court was whether the person prosecuted in a criminal case, abducted by U.S. officials of Mexico’s territory, may be tried before a U.S. court for an offense under the criminal law of the United States, while there is a bilateral extradition treaty binding both of the countries. As the U.S. Supreme Court stated in its ruling that international kidnapping in US-Mexico relations is not prohibited, there is a question how acts of abduction may be assessed in U.S. relations with other countries, e.g. Poland.
Keywords: international kidnapping; abduction; Alvarez-Machain; extradition; Mexico; criminal law; international treaty